A Theoretical Assumption of Atrial Fibrillation - Tilman, Vladimir (New Horizons in Medicine and Medical Research Vol. 9, 2022)
In clinical practice, atrial fibrillation (AF) is the most frequent heart arrhythmia. Many studies have looked at what causes AF to develop, yet the subject remains unresolved. Atrial fibrillation has recently been proposed as a protective physiological mechanism based on the termination of atrial mechanical systole. This reduces the pressure in the system of the pulmonary veins and alveolar capillaries in pathological situations, and thus reduces the likelihood for development of pulmonary congestion and edema. This hypothesis explains the relationship between left ventricle (LV) dysfunction and AF, helps to build algorithms of relationships between AF and LV dysfunction, and with various diseases and conditions, suggests a new approach to the location of the source of AF and shows a protective function of the atriums in the development of LV dysfunction. The hypothesis is well correlated with the known facts and phenomenon associated with AF. The proposed hypothesis can suggest a scenario for the development of AF. Each individual has a protective physiological mechanism in the pulmonary veins, most likely genetically programmed. Atrial fibrillation (AF) is the most prevalent arrhythmia in clinical practice, and it is frequently linked to LV dysfunction and heart failure (HF). It's been dubbed "the century's epidemic." AF is a type of arrhythmia that is particularly common in the elderly, and its prevalence is increasing as the population ages. Aside from age, there are a slew of cardiac and medical problems that have been connected to AF. Hypertension, coronary artery disease, heart failure, valvular heart disease, hyperthyroidism, and other conditions fall under this category.